Addressing the Paradox – the Divergence Between Smallholders' Preference and Actual Adoption of Agricultural Innovations - Iiyama, Miyuki; Mukuralinda, Athanase; Ndayambaje, Jean Damascene; Musana, Bernard; Ndoli, Alain; Mowo, Jeremias G.; Garrity, Dennis; Ling, Stephen; Ruganzu, Vicky (Taylor and Francis, 2019)
Experiences in smallholder contexts indicate frequent mismatches between technologies introduced and needs of farmers who must make complex decisions in reallocating their limited resources under highly risky ecological and market contexts. This study proposes a cost- and time-effective, easy-to-implement approach to identify farmers’ priorities and critical intervention areas, and presents its application in guiding an agroforestry strategy in Rwanda. It was found that different tree species have distinctive enabling vs. constraining conditions under different agroecological contexts in the perspective of smallholder farmers. Tree species preferred by farmers were not necessarily widely adopted if multitudes of conditions were not enabling. The essential conditions for sustainable adoption include: quality materials/inputs are available; technologies are compatible with existing local farming systems; they are resilient to climate risks/resistant to pests-diseases; management is not complicated; and, there is guaranteed access to markets. The results show that there will not be a silver bullet national strategy to scale up agroforestry. Instead a matrix kind of strategies -to promote enabling conditions and address constraining conditions for priority species in specific agroecologies- will be required. The proposed concept should be further refined for wider agricultural technology transfer debates to break the myths of low uptakes by smallholders.